Long-term outcome after ischemic stroke in relation to comorbidity – An observational study from the Swedish Stroke Register (Riksstroke). (March 2020) - Sennfält, Stefan; Pihlsgård, Mats; Petersson, Jesper; Norrving, Bo; Ullberg, Teresa
Purpose: Comorbidity in stroke is common, but comprehensive reports are sparse. We describe prevalence of comorbidity and the prognostic impact on mortality and functional outcome in a large national ischemic stroke cohort. Methods: We used outcome data from a long-term follow-up survey conducted in 2016 by the Swedish Stroke Register (Riksstroke). Those included in the study were 11 775 pre-stroke functionally independent patients with first-ever ischemic stroke followed up at three months and 12 months (all patients), and three years (2013 cohort) or five years (2011 cohort). Pre-stroke comorbidity data for 16 chronic conditions were obtained from the Swedish National Patient Register, the Swedish Prescribed Drugs Register and the Riksstroke register. Individuals were grouped according to number of conditions: none (0), low (1), moderate (2–3) or high (≥4). Co-occurrence was analysed using hierarchical clustering, and multivariable analyses were used to estimate the prognostic significance of individual conditions. Results: The proportion of patients without comorbidity was 24.8%; 31.8% had low comorbidity; 33.5% had moderate comorbidity and 9.9% had high comorbidity. At 12 months, the proportion of poor outcome (dead or dependent: mRS ≥3) was 24.8% (no comorbidity), 34.7% (low), 45.2% (moderate) and 59.4% (high). At five years, these proportions were 37.7%, 50.3%, 64.3%, and 81.7%, respectively. There was clustering of cardiovascular conditions and substantial negative effects of dementia, kidney, and heart failure. Conclusion: Comorbidity is common and has a strong impact on mortality and functional outcome. Our results highlight the need for health systems to shift focus to a comprehensive approach in stroke care that includes multimorbidity as a key component.